An Experimental Investigation of Temperature Distribution and Joint Properties of Al 7075 T651 Friction Stir Welded Aluminium Alloys. (2016) - Shah, P.H.; Badheka, Vishvesh
Abstract: The 7xxx series aluminum alloys provides the highest strength of all aluminum alloys and are considered to be a family of high strength aerospace alloys. Its weldability with conventional fusion welding techniques is extremely poor. The development of friction stir welding (FSW) process has made these aluminum alloys join satisfactorily in a reliable manner. The heat generation during the process dictates the weld quality, the tool life and the residual stresses in the workpiece. The tool geometry plays a vital role in the determining the amount of heat generation during FSW. In the present work, different tool shoulder diameters were used to practically explore the thermal histories in the workpiece during the FSW process of Al 7075 T651 joints. The transient temperatures during FSW were measured with different thermocouple layouts. A detailed discussion on temperature distributions in the workpiece is presented. Evaluation of the tensile strength of the welded joints was carried out alongwith the metallographic characterization and they were put in relation with the temperature data recorded during the friction stir welding process.